Special Higher and Secondary Education in the Military Patriotic Education (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the role of educating young people in the spirit of military patriotism, military patriotism education in higher and secondary special education institutions - the activity of our state was highlighted. Revising the preparation of young people for the defense of the Motherland requires full use of the substantive and organizational-methodical aspects of military patriotism education. It is necessary to analyze the effectiveness of educational activities, to select and strengthen the traditional forms of military patriotism given and verified by practice, to search for new forms that more fully implement the tasks of preparing young people for the defense of the Motherland in modern conditions.